Business intelligence : an overview of the process and its applications to healthcare - Santos, Pedro Miguel Paiva França (2018)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2016